The emerging role of triggering receptor expressed on myeloid cell-2 in malignant tumor - Yahui Wang; Ying Chu; Fenghua Cao; Zhihong Chen; Huaxi Xu; Shengjun Wang; Jie Ma (Central European Journal of Immunology, 2023)
Triggering receptor expressed on myeloid cell-2 (TRE M2) is a transmembrane receptor which is specifically expressed on myeloid cells. To date, TRE M2 has been confirmed as a key factor in many pathologies, such as Alzheimer’s disease, obesity-related metabolic syndrome, fatty liver and atherosclerosis. However, the role of TRE M2 in tumors remains poorly understood. TRE M2 is highly expressed in more than 200 primary and metastatic tumors, a feature that makes TRE M2 a potential clinical target for tumor immunotherapy. The tumor microenvironment (TME) is the “soil” which tumors survive on and exhibits immunosuppressive characteristics. During the development of a tumor, TME will secrete various chemotactic factors to recruit myeloid cells. It is clear now that cancer progression and metastasis depend on the interactions between cancer cells and myeloid cell infiltration in TME. As an important receptor involved in inflammatory suppression signaling pathways, TRE M2 may play an important role in immune escape by the tumor. Recently, several studies have illustrated that TRE M2 expressed on tumor infiltrated myeloid cells acts as a crucial regulator of the antitumor immune response. In this review, we systematically summarize recent publications about the latest advances in knowledge of TRE M2 in cancer, especially focusing on its role in tumor associated myeloid cells and tumor immunotherapy.